Deutsch von außen - Stickel, Gerhard (De Gruyter, 2019)
What is the status and image of German in comparison to otherlanguages? What role does German play as an academic teaching andresearch subject in non-German-speaking countries? The papers inthis volume examine contemporary and historical external views ofthe German language. The authors are specialists in German studiesfrom outside the German-speaking world, together with a few fromwithin Germany.
German